Development of PBL-Based E-Book Teaching Materials on Occupational Health and Safety and Work Culture - Yasha A. Lumbantobing; Harun Sitompul; Enny Keristiana Sinaga (CV. Media Inti Teknologi, 2026)
Background: Vocational learning in Occupational Health and Safety, Environmental Health, and Work Culture requires instructional approaches that emphasize procedural understanding, safety awareness, and problem-solving skills. However, learning practices in many vocational schools still rely on conventional media, resulting in limited student engagement and suboptimal learning outcomes.Aims: This study aimed to develop a Problem-Based Learning (PBL)-based e-book and examine its validity, practicality, and effectiveness as an instructional solution for K3LH and Work Culture learning.Methods: This study employed a Research and Development (R&D) approach using the ADDIE model. The e-book was designed by integrating authentic workplace problems, visualized safety procedures, structured PBL stages, and performance-based assessments. Validation was conducted by material, media, and instructional design experts. Product testing included individual trials, small-group trials, and field implementation. Data were analyzed using normality and homogeneity tests, followed by an independent samples t-test.Results: The e-book demonstrated high validity, with a material expert score of 95.60%. Practicality testing showed very high ratings from teachers (96.67%) and students (94.89%). Effectiveness analysis indicated a significant difference in learning outcomes between the experimental and control groups (t = 5.79 > tₜₐᵦₗₑ = 2.00). The findings suggest that the e-book improves safety-oriented understanding and work attitudes, although advanced practical skills require additional simulation support.Conclusion: The PBL-based e-book is an effective instructional medium that enhances active learning and improves learning outcomes in vocational education, particularly in K3LH and Work Culture.